Indicators of angiogenesis in pregnant women with arterial hypertension - Deinichenko, O. V.; Krut, Yu. Ya.; Siusiuka, V. H.; Pavlyuchenko, M. I.; Дейніченко, Олена Валеріївна; Круть, Юрій Якович; Сюсюка, Володимир Григорович; Павлюченко, Михайло Іванович (My University, 2022)
Summary. The role of the factors of angiogenesis and hormones of pregnancy in pregnant women with hypertension has been studied inadequately and their interaction in such patients is not fully elucidated at present time. Aim. To detect peculiarities of angiogenesis factors and placental hormones in pregnant women with arterial hypertension I and II grades in comparison with results of healthy pregnant women. Materials and methods. Conducting a prospective study of 88 pregnant women, which included: analysis of clinical and anamnestic characteristics and study of the peculiarities of pregnancy in women with chronic hypertension in the first trimester of pregnancy (11-12 weeks). The open prospective controlled study involved 61 pregnant women with chronic arterial hypertension (CAH) 1-2 degree, who were included in the first - the main group. The second control group included 27 healthy pregnant women with physiological pregnancies. Among the angiogenesis indices, the placental growth factor (PlGF), as a pro-angiogenic factor and placental soluble fms-like tyrosine kinase (sFlt-1) was determined as an anti-angiogenic factor, sFlt-1/PlGF ratio was also estimated. Statistical analysis was done by using «STATISTICA® for Windows 6.0» (Stat Soft Inc., № AXXR712D833214FAN5).
Keywords: factors of angiogenesis; pregnancy; arterial hypertension